KREATIVITAS GURU, KETERSEDIAAN LITERATUR, DAN SOFT SKILL PENGARUHNYA TERHADAP MINAT BERWIRAUSAHA - Rahmatullah; Nur Halim (ILIN Institute, 2021)
This study aims to determine and analyze the effect of teacher creativity, the availability of literature and soft skills on interest in entrepreneurship. The research method used is a quantitative method. Data collection methods are through observation, questionnaires or questionnaires and documentation. The number of samples in this study were 94 students from 7 majors at SMK Negeri 1 Pangkep then analyzed using multiple linear regression analysis. Based on the results of the study, it shows that the results of tests carried out simultaneously, the three variables (X) have a positive effect on the growth of entrepreneurial interest in students of SMK 1 Pangkep (Y). However, partially the teacher creativity variable (X1) does not have a significant effect, while the other two variables, namely the availability of literature (X2) and soft skills (X3), have a significant effect on the growth of students' entrepreneurial interest (Y).